mRNA-based platform for preventing and treating Staphylococcus aureus by targeted staphylococcal enterotoxin B - Luo, Fumei; Xu, Chuanfei; Zhang, Chengwen; Tan, Aomo; Lu, Dongshui; Luo, Ping; Cheng, Ping; Zhang, Weijun; Bai, Lijuan; Yu, Cuiyun; Sun, Si; Zeng, Hao; et al. (Frontiers in Immunology, 2024)
Staphylococcus aureus (S. aureus) possesses numerous virulence factors, with the increasing prevalence of drug-resistant strains heightening the threat posed by this pathogen. Staphylococcal enterotoxin B (SEB), a highly conserved toxin secreted by S. aureus, is also recognized as a potential bioweapon with super-antigenic activity. SEB represents a promising target in efforts to combat infections caused by S. aureus. We developed mRNA-based vaccine and antibody targeting SEB for both prophylactic and therapeutic purposes in varying S. aureus infection conditions. The mSEB mRNA vaccine (10 μg per mouse) induces more robust and persistent immune responses, including higher antibody titers and specific cellular immune responses, compared to immunization with 30 μg of mSEB protein adjuvanted with aluminum phosphate. Additionally, the anti-SEB mRNA antibody maintains secretion of anti-SEB monoclonal antibody (mAb) with a dosage that is 10 times lower than purified protein administration. The mRNA-based antibody exhibits superior pharmacokinetic profiles compared to its protein counterparts, efficiently neutralizing SEB and clearing S. aureus from circulation. Both the mRNA vaccine and mRNA antibody demonstrate preventive and therapeutic effects by eliciting specific immune responses and generating high-affinity antibodies in mice. We have laid the groundwork for the development and evaluation of mRNA-based vaccines and antibodies targeting SEB produced by S. aureus. Our studies demonstrate that these approaches are more effective than traditional protein-based vaccines and antibodies in terms of inducing immune responses, pharmacokinetics, and their prophylactic or therapeutic efficacy against S. aureus infections.